Hospitality and Amnesty: Aravind Adiga’s Narrative of Legal Liminality - Mendes, Ana Cristina (2022)
Amnesty continues several of the social justice themes of precarity and subalternity (at times, a violent subaltern agency) of Aravind Adiga’s fiction, and its literary narrative centres again on criminal acts and the moral dilemma the protagonist faces over whether to report a murder and expose his illegality to do “the right thing.” Offering a postcolonial reading of Amnesty supported by concepts from migration, citizenship, and human rights studies, this essay discusses the novel’s representation of the inhospitable conditions experienced by migrants victimized by the precarity of their status, whether discursively categorized as illegal, irregular, undocumented, unauthorized, or unlawful; by the consequent exploitations and abuse without recourse to justice; and by the suspension of their human rights. The theme of illegality is approached in Adiga’s narrative from a more radical perspective of liminality – the state of “legal liminality” in which irregular migrants find themselves when longing to belong in the host country, or at least be legalized, while gripped and besieged by myriad daily fears and anxieties that their legal status will be discovered, compounded by a resolute refusal to leave the host country. Adiga forces this theoretical question of legal liminality to an extreme by presenting a protagonist who, as an irregular migrant, has committed the political crime of illegally overstaying in the host country. The central question of amnesty is raised when the protagonist faces the dilemma of stepping up to civic responsibilities without having been conceded participatory rights.